Self-perceived health in functionally independent older people: associated factors. Issue 1 (December 2016) - Machón, Mónica; Vergara, Itziar; Dorronsoro, Miren; Vrotsou, Kalliopi; Larrañaga, Isabel
Abstract Background Self-perceived health (SPH) is a powerful indicator of the health status of elderly people. This issue has been widely studied in oldest populations considering altogether functionally independent and dependent individuals. The objective of this study was to describe SPH and to identify the main factors that have an impact on SPH in a sample of functionally independent community-dwelling older adults. Methods For this cross-sectional study, face-to-face interviews were carried out with non-institutionalized functionally independent older individuals in a northern region of Spain. Participants were asked: "Overall, you would say that your health is excellent, very good, good, fair or poor?". SPH responses were grouped in two categories: good and poor. Binary logistic regression was used to identify factors associated with poor SPH. Results A sample of 634 individuals was studied, of whom 55 % were women. The mean age was 74.8 (SD 6.7) years. About 18 % of the respondents rated their health as poor. In the multivariate model adjusted for age and sex, reported poor health was significantly associated with polypharmacy (≥3 drugs per day) (OR: 5.76, 95 % CI: 3.60–9.18), the presence of sensory impairment (OR: 1.87, 95 % CI: 1.15–3.04), bad sleep quality (OR:1.82, 95 % CI: 1.02–3.28), a bad nutrition pattern (OR: 2.37, 95 % CI: 1.08–5.21), not engaging in cognitively stimulating activities (OR: 4.08, 95 % CI: 1.64–10.20), or group social activities (OR: 2.62, 95 % CI: 1.63–4.23). Conclusions The study indicates that several health and social variables are strongly related to SPH in independent community-dwelling older adults. This finding highlights the need for thorough assessment of factors related to SPH in older independent adults, this being essential to develop health-related programmes for promoting active and healthy ageing and to delay the onset of dependence in this population.